Nucleolipid Acid-Based Nanocarriers Restore Neuronal Lysosomal Acidification Defects - Brouillard, Mathias; Barthélémy, Philippe; Dehay, Benjamin; Crauste-Manciet, Sylvie; Desvergnes, Valérie (Frontiers in Chemistry, 2021)
Increasing evidence suggests that lysosomal dysfunction has a pathogenic role in neurodegenerative diseases. In particular, an increase in lysosomal pH has been reported in different cellular models of Parkinson's disease. Thus, targeting lysosomes has emerged as a promising approach. More specifically, regulating its pH could play a central role against the neurodegeneration process. To date, only a few agents specifically targeting lysosomal pH are reported in the literature, partly due to the challenge of crossing the blood-brain barrier (BBB), preventing drug penetration into the central nervous system (CNS). To develop chronic treatments for neurodegenerative diseases, crossing the BBB is crucial. We report herein the conception and synthesis of an innovative DNA derivative-based nanocarrier. Nucleolipids, carrying a biocompatible organic acid as an active ingredient, were designed and synthesized as prodrugs. They were successfully incorporated into an oil-in-water nanoemulsion vehicle to cross biological membranes and then release effectively biocompatible acidic components to restore the functional lysosomal pH of neuronal cells. Biological assays on a genetic cell model of Parkinson's disease highlighted the non-toxicity of such nucleolipids after cellular uptake and their ability (at c=40 µM) to fully restore lysosomal acidity.